Aggravating effects of alcohol outlet types on street robbery and aggravated assault in New York City - Feng, Shun Q. (Journal of crime and justice, 2019)
The present study uses Risk Terrain Modeling (RTM) to analyze how nine different alcohol outlet types differentially influence the likelihood of aggravated assault and street robbery at micro-level places in New York City. Separate models were conducted for each of New York’s five boroughs to account for the differing environmental characteristics across the city. Results suggest that spatial influence of crime risk differed across alcohol outlet types, with off-premise grocery stores having the largest influence on the likelihood of both aggravated assault and street robbery and on-premise bars/taverns having a strong influence only on the likelihood of street robbery. In addition, although certain alcohol outlets affected crime in each borough, the spatial influence of others was more volatile. It is clear not all alcohol outlet types are equally criminogenic across boroughs. Thus, crime reduction efforts should be unique and localized according to the risk associated with outlet types and place.